Remote Work at Home as a Subject of Control by the National Labour Inspectorate - Makowski, Dariusz (Acta Universitatis Lodziensis. Folia Iuridica, 2025)
Remote work at home, due to the place of work, may raise doubts regarding the powers of the National Labour Inspectorate. The question arises whether remote work performed at home is subject to control by the Inspectorate, and if so, whether the control can be carried out at the place of work – at the employee’s home. The provisions of the Labour Code regarding remote work do not regulate this matter. In search of answers to these questions, the article analyzes the relevant regulations of international law, the Constitution of the Republic of Poland and the Act on the National Labour Inspectorate. It leads the author to conclude that it is advisable for the legislator to confirm the right of the National Labour Inspectorate to control work performed at home, as well as to regulate the conditions for conducting such a control.